Analysis approach for coupling between membrane structures and granular systems combining finite particle method (FPM) and discrete element method (DEM) - Zheng, Yanfeng; Su, Yiyang; Li, Siyuan; Zhang, Jingyao; Yang, Chao; Luo, Yaozhi (Engineering structures, 2025)
The coupling between membrane structures and granular systems (such as sand, snow, hail, etc.) may readily induce the bagging effect of membrane structures, which should be considered in structural design and analysis. In this study, an analysis method for coupling between membrane structures and granular systems is proposed based on Finite Particle Method (FPM) and Discrete Element Method (DEM). Firstly, the analysis method of membrane structures based on FPM is depicted, in which the equations of motion of particles and the process of fictitious reverse motion to obtain pure deformation are presented. Subsequently, the approach for the analysis of granular systems based on DEM is introduced, and the contact search among grains and the calculation of granular contact forces are given. Moreover, the coupling approach is proposed, in which an enhanced point-to-surface contact search algorithm is proposed. The algorithm can prevent the omission in counting or double-counting of grains encountered in the conventional projection-based algorithm. Specifically, the algorithm is implemented through three steps: (1) delimiting the control range of each membrane element, (2) calculating the local coordinate of each grain by the inverse isoparametric mapping, and (3) determining the contact force according to these local coordinates. The effectiveness of this enhanced contact search algorithm is demonstrated through a validation test. An example of a rectangular membrane structure subjected to falling grains is also analyzed to demonstrate the effectiveness of the proposed analysis approach, and the influences of the numbers of grains and membrane elements on the results are also discussed. •Coupling analysis method for membrane structures and granular systems is proposed.•An enhanced point-to-surface contact search algorithm is presented.•A validation test and a large-scale granule-falling example are conducted.•Influences of the numbers of granules and membrane elements are discussed.